Understanding cancer survivors' reasons to medicate with cannabis: A qualitative study based on the theory of planned behavior. (17th October 2020) - McTaggart‐Cowan, Helen; Bentley, Colene; Raymakers, Adam; Metcalfe, Rebecca; Hawley, Philippa; Peacock, Stuart
Abstract: Background: Prior to nonmedical cannabis legalization in Canada, individuals were only able to access cannabis legally through licensed producers with medical authorization. Now with an additional legal access system designed for nonmedical purposes, it is unclear what factors influence cancer survivors' decisions to medicate or not medicate cannabis as a complementary therapy to alleviate their cancer symptoms. Methods: We recruited cancer survivors via social media. Interested individuals were purposively sampled to ensure maximization in terms of age, sex, and province of residence. Constructs of the Theory of Planned Behavior were explored during the telephone interviews as participants described what influenced their decisions to medicate or not medicate cannabis to manage their symptoms. Results: Interviews were conducted with 33 cancer survivors. All individuals believed that cannabis would manage their cancer symptoms. Those that chose to medicate with cannabis provided a variety of reasons, including that cannabis was a more natural alternative; that it reduced their overall number of prescription drugs; and that safer products had become available with the legalization of nonmedical cannabis. Some individuals also indicated that support from physicians and validation from family and friends were important in their decision to medicate with cannabis. Individuals who opted not to medicate with cannabis raised concerns about the lack of scientific evidence and/or possible dependency issues. Some also felt their physician's disapproval was a barrier to considering cannabis use. Conclusions: The findings revealed that recreational legalization made using cannabis appear safer and easier to access for some cancer survivors. However, physicians' censure of cannabis use for symptom management was a barrier for survivors considering its use. Abstract : This manuscript illustrates the findings from individual interviews conducted with Canadian cancer survivors to explore their reasons to use cannabis as a complementary therapy to manage their cancer symptoms. In Canada, we have a unique opportunity to study the impact of country‐wide recreational legalization of access to non‐medical cannabis on cancer survivors' attitudes toward use of those substances. We used the theory of planned behaviour as the decision‐making model to understand intention and behaviour of cancer survivors regarding cannabis. The findings from our work will better inform healthcare providers how to support their patients regarding cannabis medication and to promote person‐centred and informed decision‐making.